Application of Microwave-Assisted Extraction Method to Improve Yield and Qualityof White Pepper (Piper Nigrum L) Oleoresin. - Annisa Purnamasari Damanik; Edy Hartulistiyoso; Rokhani Hasbullah (Jurnal Keteknikan Pertanian, 2022)
Oleoresin extraction is generally carried out by conventional maceration method, which takes up to 7 hours. Microwave-assisted maceration extraction method has the potential to reduce extraction time and solvent consumption. This study aims to examine the effect of applying the microwave-assisted extraction method on the yield and quality of oleoresin. The material used in this study was white pepper. Microwave maceration extraction as the main treatment was carried out by dissolving 200 grams of white pepper powder (60 mesh) with 800 mL ethanol (1:4), at a power of 100 watts, a maximum temperature of 50 oC, with 4 extraction times (30 minutes, 60 minutes, 90 minutes, and 120 minutes). Extraction by conventional maceration (7 hours) was performed as a comparison. The results of this study indicate that the microwave maceration extraction method produces a higher yield than the conventional maceration method. The average yield of microwave maceration extraction for 30, 60, 90, and 120 minutes were 8.76 %, 8.32 %, 9.46 %, and 10.37 %, respectively, higher than conventional maceration (8.61 %). The quality of white pepper oleoresin extracted by microwave maceration is different from conventional maceration in terms of the type and amount of oleoresin components. It can be concluded that the microwave maceration extraction method is effective in increasing the yield and quality of white pepper oleoresin compared to conventional maceration.